1991
DOI: 10.1016/0735-1097(91)90942-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of platelets, thrombin and hyperplasia in restenosis after coronary angioplasty

Abstract: Coronary angioplasty has become a successful and widely used treatment for patients with coronary artery disease since its first clinical application in 1977. The primary success rate has improved despite the increase in procedure and case complexity. However, acute reocclusion and late restenosis, which constitute the most important problems after successful angioplasty, continue to occur in about 5% and 35% of patients within 3 to 6 months, respectively. Angioscopic and pathologic observations have suggested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
78
0
6

Year Published

1996
1996
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(84 citation statements)
references
References 68 publications
0
78
0
6
Order By: Relevance
“…Thus, where GPIIb-IIIa blockers mainly prevent platelet aggregation, interruption at an earlier stage by a GPIb blocker is expected not only to limit the platelet plug that is formed but also to reduce additional platelet-dependent effects, such as granule release, thought to play a role in the development of arteriosclerosis and restenosis. 40,41 There are also indications that the GPIb-IX-V complex is involved in platelet-platelet interactions. Ruggeri et al 42 recently reported that blocking the GPIb-vWF interaction, after platelets from PPACK-anticoagulated blood had adhered to bovine collagen in vitro for 100 seconds at 1500 s Ϫ1 , prevented further thrombus growth measured after another 740 seconds, even at low shear rates that do not normally initiate vWF-dependent platelet adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, where GPIIb-IIIa blockers mainly prevent platelet aggregation, interruption at an earlier stage by a GPIb blocker is expected not only to limit the platelet plug that is formed but also to reduce additional platelet-dependent effects, such as granule release, thought to play a role in the development of arteriosclerosis and restenosis. 40,41 There are also indications that the GPIb-IX-V complex is involved in platelet-platelet interactions. Ruggeri et al 42 recently reported that blocking the GPIb-vWF interaction, after platelets from PPACK-anticoagulated blood had adhered to bovine collagen in vitro for 100 seconds at 1500 s Ϫ1 , prevented further thrombus growth measured after another 740 seconds, even at low shear rates that do not normally initiate vWF-dependent platelet adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Neointimal formation after vascular injury reflects migration of SMCs from the media to the intima within the arterial wall, proliferation of SMCs in the intima, and excessive production of ECM by SMCs. 13 A number of studies have reported that certain growth factors, including platelet-derived growth factor, 14 basic fibroblast growth factor, 15 interleukin-1␤, 13 and thrombin 16 derived from microthrombi, activated platelets, and leukocytes or the injured ECs themselves, may interact with the SMCs in an autocrine or paracrine manner to promote SMC proliferation and migration, thus contributing to the neointimal formation.…”
Section: Kikuchi Et Al July 1998mentioning
confidence: 99%
“…Though the underlying processes have not yet been fully elucidated, a special role in promoting the migration and proliferation of smooth muscle cells has been advocated for adherent platelets and resulting mural thrombi. [3][4][5] While previous studies with antiplatelet and anticoagulant agents such as aspirin, 14) aspirin plus dipyridamole, 15) warfarin, 16) heparin, 17) thromboxane A 2 receptor antagonists, 18) and the thrombin inhibitor hirudin 19) did not demonstrate positive effects after PTCA, use of the glycoprotein IIb / IIIa antagonist blocking the final common pathway of platelet aggregation resulted in fewer early ischemic complications 20) and a lower frequency of clinical manifestations of restenosis. 21) However, no follow-up angiographic data are available.…”
Section: Discussionmentioning
confidence: 89%
“…costs related to repeat intervention. In response to wall stretch and injury by balloon dilatation, elastic recoil, 12) neointimal hyperplasia, [3][4][5] and arterial remodeling 13) contribute to coronary luminal renarrowing during the first few months after PTCA. Various approaches to reduce restenosis have been tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation